A Usage Scenario Independent "Air Chargeable" Flexible Zinc Ion Energy Storage Device. Issue 19 (27th March 2019) - Ma, Longtao; Zhao, Yuwei; Ji, Xixi; Zeng, Jie; Yang, Qi; Guo, Ying; Huang, Zhaodong; Li, Xinliang; Yu, Jie; Zhi, Chunyi
Abstract: A rationally designed "air chargeable" energy storage device is demonstrated, which can be effectively charged by harvesting pervasive energy from the ambient environment. For an "air chargeable" zinc‐ion capacitor system, the system simply consists of a flexible bifunctional "U" shaped electrode (with the functions of energy harvesting and storage), a zinc metal electrode in middle, and two different polyelectrolytes (polyacrylamide and sodium polyacrylate) sandwiched between the zinc metal and "U" shaped electrode. When the zinc‐ion capacitor is exhausted, it can be quickly charged to 88% within 10 min by simply opening the sealing tape and allowing the air diffuse in. The capacitor exhausting‐air charging processes are repeated 60 times and the whole system works well. When the external power supplier is available, both the zinc‐ion capacitor and "air charging" component can be fully recovered. A large capacity (≈1000 mAh) "air chargeable" zinc‐vanadium battery is also demonstrated. The zinc‐vanadium battery can be fully charged by air in 1 h. This work offers a usage scenario independent reliable self‐chargeable power supply system as a promising approach to solve the intermittent and unpredictable nature of currently developed self‐chargeable devices. Abstract : The problem of limited battery life could be solved by integrating a self‐charging function, which might for example, harvest energy from natural sources such as solar, thermal, wind, or mechanical energies. However, these energy sources greatly depend on the usage scenario. A usage scenario independent "air chargeable" capacitor and battery is first demonstrated, which can be effectively charged by harvesting pervasive energy from the ambient environment.